الحاجة الى تكامل الحسابات الاقتصادية و البيئية - د. صالح ابراهيم الشعباني (PROSPECTIVE RESEARCHES, 2023)
The accounting income is regarded as a useful instrument for the economic analysis and planning the economic polices. It uses total national income sign, pure production and other economic signs. These signs and other accounting data which re counted , conventionally, in isolation from the costs of environment protection environmental deterioration and the running out of the natural resources are regarded deviced and the decisions based on are inaccurate. This leads researchers and governments in the developed countries and for adopt a policy of preparing complete environmental economic accounts and for this reason the accounting methods have been developed in order to imply the environmental and natural resources with their accounts. Consequently, the conventional and economic accounts have en merged with the environmental accounts by using a number of merging methods and it became clear that the integration of these accounts gives data of more creditability and appropriateness especially when they are used in economic planning for the sake of development. Depending on environmentally complete data meabs the capability of using environment plans that aim at proving the economic policies with information about environment and resources. The economy, environment and resources play a vital role in the process of development and planning the right governmental policies.